Pattern of Thrombocytopenia In Pregnancy At Teaching Hospital Of Rahim Yar Khan, Pakistan - Muhammad Bilal Ghafoor; Faiza Sarwar; Tahira Afzal Durrani; Zainab Quratulain Azher; Saleha Jabeen; Muhammad Haris Ali Khan (Journal of Rawalpindi Medical College)
Background:  Platelet count less than 150 × 109 / L is referred to as thrombocytopenia, which is the second common blood disorder in pregnancy after anemia. Although pregnancy is related with physiological variations in platelet count, however, several pathological conditions also cause thrombocytopenia showing significant impact on health of mother and her baby. The prevalence of thrombocytopenia during pregnancy is 7 to 11%. The physiological thrombocytopenia is multifactorial, related to hemodilution, increased platelet consumption and increased platelet aggregation.